2021
DOI: 10.3233/bd-201059
|View full text |Cite
|
Sign up to set email alerts
|

Management and outcomes of phyllodes tumours – 10 year experience

Abstract: INTRODUCTION: Phyllodes tumours represent 0.3–1% of breast tumours, typically presenting in women aged 35–55 years. They are classified into benign, borderline and malignant grades and exhibit a spectrum of features. There is significant debate surrounding the optimal management of phyllodes tumour, particularly regarding appropriate margins. METHODS: This is a retrospective review of a prospectively maintained database of patients who underwent surgical management for phyllodes tumours in a single tertiary re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The ability to distinguish between these two tumors preoperatively can not only aid in the intraoperative planning for determining proper excisional margins and management of the axilla but can also help to prevent overtreatment or undertreatment of the patient [ 4 , 5 ]. Wide surgical margins of at least 1 cm were originally thought to be optimal for local control [ 3 , 6 , 7 ]. Other studies have shown that the strongest predictor of local recurrence is the presence of tumor cells along the resection margin [ 3 , 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The ability to distinguish between these two tumors preoperatively can not only aid in the intraoperative planning for determining proper excisional margins and management of the axilla but can also help to prevent overtreatment or undertreatment of the patient [ 4 , 5 ]. Wide surgical margins of at least 1 cm were originally thought to be optimal for local control [ 3 , 6 , 7 ]. Other studies have shown that the strongest predictor of local recurrence is the presence of tumor cells along the resection margin [ 3 , 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wide surgical margins of at least 1 cm were originally thought to be optimal for local control [ 3 , 6 , 7 ]. Other studies have shown that the strongest predictor of local recurrence is the presence of tumor cells along the resection margin [ 3 , 6 , 7 ]. The ambiguity in surgical guidelines makes it difficult for the physician to decide the extent of resection for the tumor to best prevent local recurrence and avoid the need for another operation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4,5 However, there are differences in therapy and prognosis in FAs and PTs. 6 Phyllodes tumors have several types of lesions with different clinical behavior, namely benign, borderline and malignant phyllode based on histopathological features that are in accordance with the classification of WHO recommendations. 1,7,8. There are several recent findings that significantly explain the pathomechanism of fibroepithelial tumors, and support FA as a pure neoplasm.…”
Section: Introductionmentioning
confidence: 91%